-5(2b+2)+(11b-5)=0

Simple and best practice solution for -5(2b+2)+(11b-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2b+2)+(11b-5)=0 equation:


Simplifying
-5(2b + 2) + (11b + -5) = 0

Reorder the terms:
-5(2 + 2b) + (11b + -5) = 0
(2 * -5 + 2b * -5) + (11b + -5) = 0
(-10 + -10b) + (11b + -5) = 0

Reorder the terms:
-10 + -10b + (-5 + 11b) = 0

Remove parenthesis around (-5 + 11b)
-10 + -10b + -5 + 11b = 0

Reorder the terms:
-10 + -5 + -10b + 11b = 0

Combine like terms: -10 + -5 = -15
-15 + -10b + 11b = 0

Combine like terms: -10b + 11b = 1b
-15 + 1b = 0

Solving
-15 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 1b = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 1b = 0 + 15
1b = 0 + 15

Combine like terms: 0 + 15 = 15
1b = 15

Divide each side by '1'.
b = 15

Simplifying
b = 15

See similar equations:

| -5x-4(-7x+13)=132 | | 2x=(21-x)+3 | | 0.4x-.36x=2 | | 4x+360=720 | | 4x+180=720 | | 0.3x+0.3=0.4-0.6x+0.4 | | 4a^4-37a^2+9=0 | | 4t^2+21t+27=0 | | 5x-8x+10x=28-10x+3x | | 0.333333333333333x+0.333333333333333=0.4-0.666666666666667x+0.4 | | 5x-8x+10x=28-10x+3 | | 10-2x=62 | | -3(2x+11)-22=-2(x+12)+9 | | 1x+3=2x+5 | | -5x-4(-7+13)=132 | | 9a^4-52a^2+64=0 | | 5x-3(2x+4)=-17 | | 2x+4(-2x+12)=6 | | 6x+2(5x+3)=134 | | 4+c=16 | | 4x+13x+9X= | | fg(2)= | | 1+x+3=15+x | | fg(x)= | | 5(x-1.3)=9.3 | | -8-2x=12-7x | | 0.2x=-10 | | 1.5r-5=.5r | | h-g(x)= | | 3x=2(20-x) | | 3x-4y=-1 | | 8+5x=44+1 |

Equations solver categories